Analysis of Acceptance Factors of Job Portal Applications for Job Seekers in Indonesia Using TAM - Prakarsa, Graha; Nursyanti, Reni; Baransano, Esar Samuel (Universitas Muhammadiyah Magelang, 2024)
This research is based on the problem of the high number of job portal application users which is supported by the large number of job seekers in Indonesia. This research aims to determine the acceptance of job portal applications for job seekers in Indonesia with external factors, information quality and system quality. This research uses quantitative methods with the data analysis technique used is PLS-SEM using smartPLS 3.2.9 software. Data collection was carried out by distributing online questionnaires to job portal application users in Indonesia and involving 610 respondents. Based on the results of the data analysis that has been carried out, it can be seen that information quality and system quality have a positive and significant influence on perceived usefulness and the magnitude of the influence is 58.8%, information quality and system quality have a positive and significant influence on perceived ease of use and magnitude. The influence is 56.4%, perceived usefulness and perceived ease of use have a positive and significant influence on continuance intention to use and the magnitude of the influence is 63.8% and continuance intention to use has a significant positive influence on actual system use. Overall, information quality and system quality play a role in influencing actual system use indirectly.